Welfare Implications of HIV/AIDS - Haacker, Markus (IMF Working Papers; Working Paper, 2003)
The paper evaluates the impact of HIV/AIDS on welfare in several countries affected by the HIV/AIDS epidemic. Unlike studies focusing on the impact of HIV/AIDS on GDP per capita, we evaluate the impact of increased mortality using estimates of the value of statistical life. Our results illustrate the catastrophic impact of HIV/AIDS in the worst-affected countries and suggest that studies focusing on GDP and income per capita capture only a very small proportion of the welfare impact of HIV/AIDS.